Effect of a 10-week yoga programme on the quality of life of women after breast cancer surgery - Andysz, Aleksandra; Merecz, Dorota; Wójcik, Aleksandra; Świątkowska, Beata; Sierocka, Kamilla; Najder, Anna (Menopause Review/Przegląd Menopauzalny, 2014)
Aim of the study : The following research is aimed at determining the effect of yoga on the quality of life of women after breast cancer surgery. Material and methods : A 10-week yoga programme included 90-minute yoga lessons once a week. To estimate the quality of life, questionnaires developed by the European Organisation for Research and Treatment of Cancer (QLQ-C30 and QLQ-BR23) were used. An experimental group consisted of 12 women who practised yoga, a control group – of 16 women who did not. Between groups there were no differences in age, time from operation and characteristics associated with disease, treatment and participation in rehabilitation. Results : Our results revealed an improvement of general health and quality of life, physical and social functioning as well as a reduction of difficulties in daily activities among exercising women. Also their future prospects enhanced – they worried less about their health than they used to before participating in the programme. As compared to baseline, among exercising women, fatigue, dyspnoea and discomfort (pain, swelling, sensitivity) in the arm and breast on the operated side decreased. Conclusions : Participation in the exercising programme resulted in an improvement of physical functioning, reduction of fatigue, dyspnoea, and discomfort in the area of the breast and arm on the operated side. Based on our results and those obtained in foreign studies, we conclude that rehabilitation with the use of yoga practice improves the quality of life of the patients after breast cancer surgery. However, we recommend further research on this issue in Poland.